Severe and moderate periodontitis are associated with acute myocardial infarction. Issue 11 (13th May 2020) - Gomes‐Filho, Isaac S.; Coelho, Julita Maria F.; Miranda, Samilly S.; Cruz, Simone S.; Trindade, Soraya C.; Cerqueira, Eneida M.M.; Passos‐Soares, Johelle S.; Costa, Maria da Conceição N.; Vianna, Maria Isabel P.; Figueiredo, Ana Cláudia M.G.; Hintz, Alexandre Marcelo; Coelho, Amanda F.; et al.
Abstract: Background: An association between periodontitis and cardiovascular disease is now well documented; however, the effect of periodontitis severity levels on this outcome, specifically on acute myocardial infarction (AMI), remains unexplored. This study investigated the association between levels of periodontitis severity (exposure) and AMI (outcome). Methods: This case‐control study, matched by sex and age, was conducted with 621 participants, with 207 individuals treated in the emergency department of Santa Izabel and Ana Nery Hospitals in Salvador, Bahia, Brazil, diagnosed with a first AMI event, and compared to 414 individuals without a diagnosis of AMI. Levels of periodontitis severity followed two criteria: (1) Center for Disease Prevention and Control and American Academy of Periodontology; (2) Gomes‐Filho et al. (2018) using criteria that also evaluated bleeding upon probing. Conditional logistic regression analysis was performed and odds ratios (ORs) and their 95% confidence intervals (CIs) were obtained. Results: The adjusted association measurements showed a positive association between both severe (ORadjusted ranged from 2.21 to 3.92; 95% CI ranged from 1.03 to 10.05) and moderate periodontitis (ORadjusted ranged from 1.96 to 2.51; 95% CI ranged from 1.02 to 6.19), and AMI, for both periodontitis diagnostic criteria. It demonstrated that among those with moderate and severe periodontitis, the chance of having AMI was approximately two to four times greater than among those without periodontitis. Conclusion: The findings demonstrate that there is an association between the severity of the periodontal condition and AMI, suggesting a possible relationship among the levels of periodontitis severity and the cardiovascular condition.